An Investigation of UWB Path Loss for Body Area Network - Sansoda, Buncha; Choomchuay, Somsak (My University, 2018)
This paper presents the investigation of body area communication channel and provide path loss evaluation by measurement compared with channel model of IEEE 802.15.6 standard. The measurement performs in ultra-wideband frequency range and setup the body in different body poster. The receive antenna is mounted on waist while transmit antenna is placed on wrist and ankle. We found trend of path loss similar as model. The results shows that transmission between the two antenna are highly attenuated when the radio wave propagates across the body. However, if the wave direction propagates along the body as waist to ankle, the path loss would slowly increase. Thus the suitable position of antenna would certainly be important with measurement result to reduce the body effect.
Keywords: Path loss; WBAN